Is patient participation in multidisciplinary tumor conferences associated with their fear of progression?. Issue 9 (24th May 2021) - Diekmann, Annika; Schellenberger, Barbara; Reck, Sebastian; Heuser, Christian; Geiser, Franziska; Wirtz, Markus; Ansmann, Lena; Ernstmann, Nicole
Abstract: Purpose: Previous studies found that some breast cancer patients in Germany are invited to participate in a multidisciplinary tumor conference (MTC) during the discussion of their own case. MTCs are regular meetings of a treatment team in which the diagnosis and treatment plan of cancer patients are discussed. Psychological consequences concerning the patients' participation in an MTC have not been examined yet. This study examines the association between patients' participation in MTC and patients' fear of progression (FoP). Methods: This analysis is part of a larger project named "Patient participation in multidisciplinary tumor conferences in Breast Cancer Care" (PINTU) which is a multicenter observational mixed‐methods study. The study was conducted in six breast and gynecological cancer centers in North Rhine‐Westphalia, Germany. Data were collected from 2018 to 2020 by patient survey at three time points. Patients with ( n  = 81) and without ( n  = 120) MTC participation were compared. FoP was measured with a 12‐item short form of the FoP Questionnaire (FoP‐Q‐SF) at all three measurement time points. Data analysis included descriptive statistics, a one‐way repeated variance analysis (ANOVA), and a one‐way repeated ANCOVA using the propensity score as a covariate. Results: Data of n  = 201 patients were included in the analysis. In general, FoP scores decreased in both groups from T0 to T2 ( F  = 36.539, p  < 0.001, η 2  = 0.155). Non‐participating patients did not differ with regard to their FoP from patients who participated in an MTC before and after participation. The results of AN(C)OVA revealed no significant effects concerning the influence of patient participation in an MTC on FoP ( F  = 0.014, p  = 0.907, η 2 = <0.001 and ( F  = 0.013, p  = 0.909, η 2 = <0.001). Conclusion: Since the FoP is not influenced by participation, the findings do not support recommendations for or against patient participation in an MTC. Further research should focus on the question of which patient groups might benefit from participation in an MTC with regard to which outcome variables.